Celiac Disease Presenting as Recurrent Pancreatitis and Pseudocyst - Basha, Jahangeer; Appasani, Sreekanth; Vaiphei, Kim; Singh, Kartar; Kochhar, Rakesh (JOP. Journal of the Pancreas, 2012)
Context The association between celiac disease and pancreatitis is sparsely reported. Celiac disease may remain asymptomatic or may have atypical features, and its diagnosis in pancreatitis may not be obvious. It is more than mere chance association that explains the occurrence of pancreatitis in celiac disease. Malnutrition, papillary stenosis and immunopathogenetic mechanisms contribute to the development of pancreatitis in a patient of celiac disease. Case report We here report one such case that had recurrent acute pancreatitis with pseudocyst formation and negative routine etiological work up. It was on noticing abnormal duodenal mucosa at the time of doing endoscopic cystogastrostomy that the diagnosis of celiac disease was suspected and later proved. Conclusion This report highlights that celiac disease should be considered in the etiological work up of patients with unexplained pancreatitis. Image: Endoscopic image from second part of the duodenum showing grooving and nodularity in the duodenum.